College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter P - Prerequisites: Fundamental Concepts of Algebra - Exercise Set P.5 - Page 75: 111



Work Step by Step

$(x-y)^{4}- 4(x-y)^{2}$ Takeout common factor $(x-y)^{2}$ $=(x-y)^{2}((x-y)^{2}-4)$ $=(x-y)^{2}((x-y)^{2}-2^{2})$ Use the formula $[(a^{2}-b^{2}) = (a+b)(a-b)]$ $=(x-y)^{2}((x-y)+2)((x-y)-2)$ $=(x-y)^{2}(x-y+2)(x-y-2)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.